Respuestas

¡La mejor respuesta!
2013-08-24T21:35:51+02:00
Alesandra,

Esa raiz viene de
                              x = (- b + - raiz delta)/2a
                              Si x1 = 1 + 3i
                                  x2 = 1 - 3i               S = {(1 - 3i), (1 + 3i)}
La otra raiz es (1 - 3i) RESPUESTA

Del desarrolo se puede ver:
                                 a = 1
                                 b = 1
             delta = b^2 - 4.a.c = - 9            [ - 9 = (3i)^2
                     = 1 - 4.1.c = - 9
                             - 4c = - 10
                                  c= 5/2
La ecuación es:
                          x^2 - x + 5/2 = 0
                          2x^2 - 2x + 5 = 0           RESULTADO FINAL